Protonation States of the Tryptophan Synthase Internal Aldimine Active Site from Solid-State NMR Spectroscopy: Direct Observation of the Protonated Schiff Base Linkage to Pyridoxal-5′-Phosphate - Caulkins, Bethany G; Bastin, Baback; Yang, Chen; Neubauer, Thomas J; Young, Robert P; Hilario, Eduardo; Huang, Yu-ming M; Chang, Chia-en A; Fan, Li; Dunn, Michael F; Marsella, Michael J; Mueller, Leonard J (Journal of the American Chemical Society, 2014)
The acid–base chemistry that drives catalysis in pyridoxal-5′-phosphate (PLP)-dependent enzymes has been the subject of intense interest and investigation since the initial identification of PLP’s role as a coenzyme in this extensive class of enzymes. It was first proposed over 50 years ago that the initial step in the catalytic cycle is facilitated by a protonated Schiff base form of the holoenzyme in which the linking lysine ε-imine nitrogen, which covalently binds the coenzyme, is protonated. Here we provide the first 15N NMR chemical shift measurements of such a Schiff base linkage in the resting holoenzyme form, the internal aldimine state of tryptophan synthase. Double-resonance experiments confirm the assignment of the Schiff base nitrogen, and additional 13C, 15N, and 31P chemical shift measurements of sites on the PLP coenzyme allow a detailed model of coenzyme protonation states to be established.